2007
DOI: 10.1021/ef070152g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Quaternary Ammonium Salts as Phase-Transfer Catalysts in the Liquid−Liquid Phase for Oxidation of Thiophene

Abstract: Owing to the insolubility of the binary phase system for oxidative desulfurization, a formic acid/H2O2 system with quaternary ammonium salts as phase-transfer catalysts was employed in the oxidation of thiophene. Four catalytic systems with ultrasound were carried out, tetrabutyl ammonium bromide behaved as the optimum active catalyst, and the desulfurization rate was 94.67%. Dispersion of phase-transfer catalyst between the organic and aqueous phases was related to the extraction constant. When the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 15 publications
3
41
0
Order By: Relevance
“…DBT in the ionic liquid phase was oxidized to its corresponding sulfone by the hydroxyl radicals. On the other hand, quaternary ammonium salts, such as tetrabutyl ammonium bromide (TBAB), can decrease the activation energy (E a ) needed in the oxidation of thiophene and thiophene derivatives, therefore the sulfur compounds showed a high reactivity and readily oxidized to the corresponding sulfone in the organic acid/H 2 O 2 (Zhao and Ren, et al, 2007). Figure 2 shows that sulfone does not exist in the oil phase because of the high polarity of the coordinated ionic liquid.…”
Section: The Process and Mechanism Of Oxidation/extractionmentioning
confidence: 99%
“…DBT in the ionic liquid phase was oxidized to its corresponding sulfone by the hydroxyl radicals. On the other hand, quaternary ammonium salts, such as tetrabutyl ammonium bromide (TBAB), can decrease the activation energy (E a ) needed in the oxidation of thiophene and thiophene derivatives, therefore the sulfur compounds showed a high reactivity and readily oxidized to the corresponding sulfone in the organic acid/H 2 O 2 (Zhao and Ren, et al, 2007). Figure 2 shows that sulfone does not exist in the oil phase because of the high polarity of the coordinated ionic liquid.…”
Section: The Process and Mechanism Of Oxidation/extractionmentioning
confidence: 99%
“…under PTC [6][7][8][9][10]. Kinetic studies of such type of oxidations using various oxidizing agents were also reported [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Among the organosulfur compounds thiophenes are the most refractory compounds in the ODS process due to their low reactivities to oxidation 3) , so development of effective oxidation methods for thiophenes is important for producing ultraclean naphtha. Several oxidation processes for thiophenes by using formic acid _ H2O2 3) , formic acid _ H2O2-phase transfer catalyst-ultrasonication 4) , formic acid _ H2O2 _ silica gel 5) , acetic acid (AcOH) _ H2O2-quaternary ammonium coordinated ionic liquid 6) , H2O2 _ Ti-containing molecular sieves 7) , H2O2 _ titanium silicate 8)~10) , H2O2 _ Au/titanium silicate 11) , and H2O2 _ molybdophosphoric acid-phase transfer catalyst 12) have been reported. We previously demonstrated that thiophenes can be oxidized with H2O2 _ tungstophosphoric acid (TPA) in both AcOH and octane/AcOH organic biphasic systems, and that the biphasic oxidative treatment is effective for the ODS of naphtha 13) .…”
Section: Introductionmentioning
confidence: 99%